Canadian Laboratory Initiative on Pediatric Reference Interval Database (CALIPER): Pediatric reference intervals for an integrated clinical chemistry and immunoassay analyzer, Abbott ARCHITECT ci8200 - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Objectives: A comprehensive set of age- and gender-specific pediatric reference intervals is essential for accurate interpretation of laboratory tests in a pediatric setting. Design and methods: 1459 serum/plasma from children attending select outpatient clinics and deemed to be metabolically stable, were collected from five age groups; 0-12 months, 1-5 years, 6-10 years, 11-14 years and 15-20 years. Samples were analyzed for 24 chemistries and 15 immunoassays on ARCHITECT ci8200. Results: Reference intervals were established according to CLSI/IFCC C28-P3 guidelines by the Robust statistical method. The ranges reflect the central 95% confidence intervals for the population tested. Age and gender were partitioned using the Harris-Boyd method. Conclusions: While these intervals are ci8200 method specific, they not only provide robust intervals for users of this system but are also useful for any laboratory requiring pediatric intervals if they can be shown to be transferable and if validated for the local patient population. (c) 2009 The Canadian Society of Clinical Chemists. Published by Elsevier Inc. All rights reserved.
Keywords: Pediatric; Children; Reference intervals; Biomarkers; Chemistry; Immunoassay; GAP ANALYSIS; ESTABLISHMENT; ADOLESCENTS; CHILDREN; VALUES